Historical and Philosophical Prerequisites for the Analysis of Cognition Objectivity in the Social Sciences - Korotkikh, Vyacheslav I. (2021)
The article deals with the analysis of the sociality construction in Hegel’s The Phenomenology of Spirit, which is the prerequisite for the development of current social and humanitarian knowledge. The author introduces the idea that a decisive factor for the formation of the Method of the Humanities and Social Sciences is Hegel’s reconsideration of the idea of the immediacy of social relations as a subject for philosophical consideration. Sociality construction, compared to the uncritical perception of Society as an object that is available for observation as a natural object, provides a consistent and methodically substantiated disclosure of the essential characteristics of social life. In The Phenomenology of Spirit, Hegel describes Sociality forms as necessary steps for the movement of the spirit toward self-cognition. Reasonable development of social relations is based on their sphere of self-consciousness attributes, which unlike the previous formations of the consciousness (die Gestalt and die Gestaltung that in various English translations are form, mode, shape, and figure) reveal that truth is not in the object but in unity with the self. Thus, the most significant discovery of the philosopher is that consciousness “pushes its boundaries” and overcomes imaginary singularity. In addition, “the doubling of consciousness” contributes to the formation of sociality as a sphere in which the spirit is capable of revealing substance concretion. The concept of sociality, which is first described in the chapter on consciousness, is revealed in the subsequent sections. As a result, social relations become the main concept of Hegel’s work. The development of this concept is not only philosophically and systematically significant. As it is presented in this article, social relations substantiate the possibility of overcoming subjective, for example, “evaluative” approaches to the consideration of social life based on the idea of the immediacy of social relations. Moreover, this concept reveals the essential nature of sociality formation and its existence in various forms of spirit. The results of this research can be regarded as verification of the provision that the method of sociality construction presented in The Phenomenology of Spirit provides cognition of social life via rational means and the argumentativeness of social and humanitarian knowledge. Thus, the foundations for the scientific study of human and society can be developed.